2022
DOI: 10.1186/s12864-022-08583-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of genetic structure and runs of homozygosity analysis in Anhui indigenous and Western commercial pig breeds using PorcineSNP80k data

Abstract: Background Runs of homozygosity (ROH) are continuous homozygous regions typically located in the DNA sequence of diploid organisms. Identifications of ROH that lead to reduced performance can provide valuable insight into the genetic architecture of complex traits. Here, we systematically investigated the population genetic structure of five Anhui indigenous pig breeds (AHIPs), and compared them to those of five Western commercial pig breeds (WECPs). Furthermore, we examined the occurrence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…In contrast, our estimates were based on a large sample size (N = 2077). On average, there were 32.2 ROH per animal in Ningxiang pigs, whereas Jiang et al [25] reported between 15.0 and 44.0 ROH in Aihui indigenous pigs. Fang et al [26] classified ROH into three length bins: 1-5 Mb, 5-10 Mb, and >10 Mb.…”
Section: Genomic Characterization and Runs Of Homozygositymentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, our estimates were based on a large sample size (N = 2077). On average, there were 32.2 ROH per animal in Ningxiang pigs, whereas Jiang et al [25] reported between 15.0 and 44.0 ROH in Aihui indigenous pigs. Fang et al [26] classified ROH into three length bins: 1-5 Mb, 5-10 Mb, and >10 Mb.…”
Section: Genomic Characterization and Runs Of Homozygositymentioning
confidence: 92%
“…Jiang et al [25] used the same five ROH categories as ours, and they reported similar ROH frequencies in Aihui indigenous pigs: 44.7-55.1% (1-5 Mb), 28.2-37.1% (5-10 Mb), 12.1-16.6% (10-20 Mb), 2.9-5.6% (20-40 Mb), and 0.1-0.7% (>40 Mb). Nevertheless, our results demonstrated a slightly higher frequency for the first category (1-5 Mb) and a lower frequency in the last category (>40 Mb).…”
Section: Genomic Characterization and Runs Of Homozygositymentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 320 blood samples were collected from 10 breeds of pigs, including 5 foreign breeds (WECP): Yorkshire (n = 50), Landrace (n = 30), Duroc (n = 30), Pietrain (n = 30), Berkshire (n = 30), and 5 indigenous Anhui pig populations (AHIP): Anqing six-end-white pig (ASP, n = 30), Wei pig (WP, n = 30), Wannan Spotted pig (WSP, n = 30), Wannan Black pig (WBP, n = 30), and Huai pig (HP, n = 30). We considered two different groups based on the results obtained in the previous study [ 20 ]. We extracted genomic DNA from ear tissues using the traditional phenol/chloroform method.…”
Section: Methodsmentioning
confidence: 99%
“…China has the most genetic resources of domestic pigs [22] , [23] . Jinhua ( JH ), Chun’an ( CA ), Longyou Black ( LY ), and Shengxian Spotted ( SX ) pigs originated in eastern China and have similar characteristics to other indigenous breeds, e.g., improved meat quality, disease resistance, and high fertility in comparison with intensively-reared commercial pig breeds (e.g., Large white, Landrace, and Duroc pig breeds) [24] , [25] , [26] . These excellent characteristics mark them as the best material to uncover the genetic mechanism of economic traits and support the sustainable development of the pig industry [27] .…”
Section: Introductionmentioning
confidence: 99%